Evidence for NADPH oxidase activation by GPR40 in pancreatic β-cells. (1st January 2020) - Nunes Marsiglio-Librais, Gabriela; Aparecida Vilas-Boas, Eloisa; Carlein, Christopher; Hoffmann, Markus Daniel Alexander; Roma, Leticia Prates; Carpinelli, Angelo Rafael
ABSTRACT: Objective: Investigate the involvement of the fatty acids receptor GPR40 in the assembly and activation of NADPH oxidase and the implications on pancreatic β-cell function. Methods: BRIN-BD11 β-cells were exposed to GPR40 agonist (GW9508) or linoleic acid in different glucose concentrations. Superoxide and H2 O2 were analyzed, respectively, by DHE fluorescence and by fluorescence of the H2 O2 sensor, roGFP2-Orp1. Protein contents of p47 phox in plasma membrane and cytosol were analyzed by western blot. NADPH oxidase role was evaluated by p22 phox siRNA or by pharmacological inhibition with VAS2870. NOX2 KO islets were used to measure total cytosolic calcium and insulin secretion. Results: GW9508 and linoleic acid increased superoxide and H2 O2 contents at 5.6 and 8.3 mM of glucose. In addition, in 5.6 mM, but not at 16.7 mM of glucose, activation of GPR40 led to the translocation of p47 phox to the plasma membrane. Knockdown of p22 phox abolished the increase in superoxide after GW9508 and linoleic acid. No differences in insulin secretion were found between wild type and NOX2 KO islets treated with GW9508 or linoleic acid. Discussion: We report for the first time that acute activation of GPR40 leads to NADPH oxidase activation in pancreatic β-cells, without impact on insulin secretion.